Higher Curvature Gravity in Large Extra Dimension: Phenomenological Implications - Tanyıldızı, Şükrü Hanif; Demir, Durmuş Ali (Izmir Institute of Technology, 2007)
This thesis is devoted to a detailed study of the higher curvature gravity and its phenomenological implications in large extra dimensions. This work is intended as a discussion of effective interactions among brane matter induced by modifications of higher dimensional Einstein gravity via the replacement of Einstein-Hilbert term with a generic function f(R) of the curvature scalar R.In this work, following the introductory chapters on extra dimensions and higher curvature gravity in large extra dimensions, we derive the graviton propagator and then we analyze impact of virtual graviton exchange on interactions among brane matter. We find that f(R) gravity effects are best probed by high-energy processes involving massivegauge bosons, heavy fermions or the Higgs boson. We perform a comparative analysis of the predictions of f(R) gravity and of Arkani.Hamed, Dimopoulos and Dvali (ADD) scenario, and find that the former competes with the latter when f00(0) is positive and comparable to the fundamental scale of gravity in higher dimensions (Demir and Tanyıldızı 2006). In addition, we briefly discuss graviton emission from the brane as well as itsdecays into brane-localized matter and we find that they hardly compete with the ADD expectations.Consequently, we discussed that possible existence of higher-curvature gravitational interactions in large extra spatial dimensions opens up various signatures to be confronted with existing and future collider experiments.
Thesis (Master)--Izmir Institute of Technology, Physics, Izmir, 2007
Includes bibliographical references (leaves: 37-40)
Text in English; Abstract: Turkish and English
vii, 50 leaves
Keywords: QC178. T16 2007; Gravitation; Gravity; Curvature; Phenomenological theory (Physics)